24 PROTEIN KINASE C DELTA MEDIATES THROMBIN-INDUCED ENDOTHELIAL BARRIER DYSFUNCTION THROUGH ACTIN STRESS FIBER FORMATION. (1st March 2005) - Chiang, E. T.; Camp, S. M.; Dudek, S. M.; Natarajan, V.; Garcia, J. G.N.
Abstract : Pulmonary endothelial cells (EC) maintain vascular barrier integrity through dynamic regulation of the actin cytoskeleton. In response to an inflammatory agonist, such as thrombin, endothelial barrier dysfunction occurs in part through actin stress fiber formation and myosin light chain (MLC) phosphorylation. Protein kinase C (PKCs) belong to a family of serine/threonine kinases, which have been implicated in barrier regulation, but the role of specific PKC isoforms in mediating thrombin-induced barrier dysfunction in human pulmonary endothelium is unclear. PKCδ is highly expressed in human lung EC and is activated in response to thrombin. Using pharmacological (rottlerin) and molecular (AdDN PKCδ) approaches to inhibit PKCδ, we assessed the role of PKCδ in regulating stress fiber formation, MLC phosphorylation, and barrier function. Inhibition of PKCδ attenuated both thrombin-induced actin stress fiber formation and endothelial barrier dysfunction, but not MLC phosphorylation. Since actin stress fiber formation and MLC phosphorylation are downstream effectors of RhoA via mDia and Rho kinase signaling pathways, respectively, we examined the relationship between RhoA and PKCδ. Overexpression of constitutive active RhoA resulted in PKCδ activation and stress fiber formation, both of which can be blocked with rottlerin treatment. In addition, Y-27632 (10 μM), a Rho kinase inhibitor, blocked thrombin-induced MLC phosphorylation and attenuated endothelial barrier dysfunction suggesting PKCδ does not signal through RhoA-Rho kinase pathway. Since PKCδ inhibition improved barrier restoration upon thrombin challenge, we next examined the effect of PKCδ inhibition on the barrier-enhancing agent, sphingosine 1-phosphate (S1P), which induces a rapid and sustained endothelial barrier enhancement. PKCδ inhibition delineates cortical actin formation and augments the S1P response. Taken together, our data demonstrate that PKCδ is a downstream target of RhoA and plays a barrier disruptive role in mediating thrombin-induced stress fiber formation and negatively regulating the barrier-enhancing response of S1P.